Elementy systemu ekspertowego w systemach do zarządzania wiedzą - Sostaric, Bożena (Elements of Export System in Knowledge Management Systems, 2005)
The main aim of this article is an analysis of knowledge based systems with elements of expert systems and their ways of development. The main example presented in this article shows an integration of expert systems with decisions support systems. The second part of this paper gives examples of integration of expert systems with enterprise management systems and systems in banking and finance sector.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1064, s. 258-267